2005
DOI: 10.1074/jbc.m504693200
|View full text |Cite
|
Sign up to set email alerts
|

Long Range Allosteric Control of Cytoplasmic Dynein ATPase Activity by the Stalk and C-terminal Domains

Abstract: The dynein motor domain consists of a ring of six AAA domains with a protruding microtubule-binding stalk and a C-terminal domain of unknown function. To understand how conformational information is communicated within this complex structure, we produced a series of recombinant and proteolytic rat motor domain fragments, which we analyzed enzymatically. A recombinant 210-kDa half-motor domain fragment surprisingly exhibited a 6-fold higher steady state ATPase activity than a 380-kDa complete motor domain fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…Note that these predictions are tightly coupled to the assumption that following ATP hydrolysis, a head containing both ADP and Pi is detached from ͑or weakly interacts with͒ the MT. Current experimental results 8,14 disagree on this issue. If future experiments confirm the high sensitivity of the motor's velocity and run length on the phosphate concentration, this result would provide indirect evidence to support the scenario in which heads containing both ADP and Pi do not interact strongly with the MT.…”
Section: Conservation Of the Mean Fluxes Requiresmentioning
confidence: 51%
See 1 more Smart Citation
“…Note that these predictions are tightly coupled to the assumption that following ATP hydrolysis, a head containing both ADP and Pi is detached from ͑or weakly interacts with͒ the MT. Current experimental results 8,14 disagree on this issue. If future experiments confirm the high sensitivity of the motor's velocity and run length on the phosphate concentration, this result would provide indirect evidence to support the scenario in which heads containing both ADP and Pi do not interact strongly with the MT.…”
Section: Conservation Of the Mean Fluxes Requiresmentioning
confidence: 51%
“…11,14 It has been shown that the motor's interaction with the MT accelerates the release of ADP in both axonemal 11 and cytoplasmic dynein, 14 which suggests that MT binding precedes ADP release.…”
mentioning
confidence: 99%
“…AAA1 has been deduced to serve as the principal site for ATP hydrolysis, based on the effects of vanadate-mediated UV photocleavage at this site (Gibbons et al, 1987;Gee et al, 1997). More recent studies on the dynein motor domain suggest that hydrolytic activity in AAA1 also requires the structural involvement of AAA2 (Takahashi et al, 2004;Höök et al, 2005). Consequently, more than half of the conserved residues are located within the boundaries of the linker and the first two AAA domains, stressing the region's significance as the source of force production within the dynein motor.…”
Section: Sequence Conservation Within Dynein Hc Functional Domainsmentioning
confidence: 99%
“…Our lab has recently investigated intramolecular regulation of dynein enzymatic activity by analysis of recombinant and proteolytic motor fragments (Höök et al, 2005). Using baculovirus infection of insect cells, we expressed a 380-kDa fragment corresponding to the entire motor domain and a 210-kDa fragment corresponding to its Nterminal half, ending just prior to the stalk (Fig.…”
Section: Evidence From Recombinant Dynein Fragments For Stalk Regulatmentioning
confidence: 99%
“…To learn more about the structural organization and intramolecular regulation of the dynein motor domain, we subjected both the 380-and 210-kDa fragments to controlled proteolytic digestion (Höök et al, 2005). Surprisingly, the number of discrete fragments that could be identiWed was very small.…”
Section: Evidence From Proteolytic Digestion For Control Of Dynein Mementioning
confidence: 99%